Journal Closure - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
JOURNAL OF INFRASTRUCTURE & FACILITY ASSET MANAGEMENT Volume 1, Issue 1, March 2019 (e) ISSN 2656-8896 (p) ISSN 2656-890X